2017
DOI: 10.1126/scisignal.aan3676
|View full text |Cite
|
Sign up to set email alerts
|

HemITAM: A single tyrosine motif that packs a punch

Abstract: Certain genetically linked C-type lectin-like receptors that activate innate immune cells variably signal through their cytoplasmic hemITAM motifs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 99 publications
(172 reference statements)
0
25
1
Order By: Relevance
“…The results shown above indicate that the β-glucan structure is an important factor in signaling outcomes. Previous research has shown that other transmembrane CTLs that also contain a (hem)ITAM domain can form homodimers before or upon ligand recognition [56, 57]. Furthermore, crystallography studies of the carbohydrate recognition domain (CRD) have shown that Dectin-1A head groups form dimers when laminarin is present [58].…”
Section: Resultsmentioning
confidence: 99%
“…The results shown above indicate that the β-glucan structure is an important factor in signaling outcomes. Previous research has shown that other transmembrane CTLs that also contain a (hem)ITAM domain can form homodimers before or upon ligand recognition [56, 57]. Furthermore, crystallography studies of the carbohydrate recognition domain (CRD) have shown that Dectin-1A head groups form dimers when laminarin is present [58].…”
Section: Resultsmentioning
confidence: 99%
“…Decreased Clec2 stability is consistent with a previous report demonstrating that tetraspanin CD37, the closest phylogenetic relative to CD82, is required for cell surface expression of a related family member, dectin-1 ( Meyer-Wentrup et al, 2007 ). Both Clec2 and dectin-1 contain hemITAM motifs that signal to Syk and Vav ( Bauer and Steinle, 2017 ). Whether Clec2 contributes to Syk and Vav signaling via integrin αvβ3 or whether it acts independently is unclear and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellularly, CLEC-2 contains a hemi ITAM (hemITAM) YxxL motif in its cytoplasmatic tail, which is similar to ITAM motifs comprising a YxxLx(6–12)YxxL sequence [ 145 , 146 ]. Upon CLEC-2 ligand binding or antibody-mediated dimerisation, Src phosphorylates hemITAM and SH2 domain-containing tyrosine kinase Syk which in turn conducts additional hemITAM motif phosphorylation and autophosphorylation [ 147 149 ].…”
Section: Involvement Of Platelet Itam and Hemi Itam Receptors In Cancmentioning
confidence: 99%